AREA LEAF OF ORANGE FLESH MELON IN FUNCTIO THE DEGREE-DAY TO TWO TILLEGE METHODS, WITH OR WITHOUT DEDS - LACERDA, VIVIANE DA S.; PAZ, KELLY K. R. DA; Maia, Celsemy Eleuterio (Revista Brasileira de Engenharia de Biossistemas, 2009)
The models that relate parameters agrometeorologicals with growth, development and yield of thecrops in different environmental help in decisions to the agricultural. With the objective of evaluate thearea leaf of the orange flesh melon to two tillage methods (entire area or strip tillage) both with orwithout beds, a field trial in a factorial scheme with four replications was developed in aQuartzipsamments. The area leaf was evaluated in function the degree-day. Considering the conditionsin which the trial was carried out, the treatments influenced in the area leaf, maximum absolute growthrate, degree-day to maximum absolute growth rate and in degree-day to 50% of the maximum area leaf.